Credit Scoring P2P Lending Fintech: Right to Explanation in AI-Based Credit - Aliya Suci Maghfirli; Thea Farina; Nuraliah Ali (Green Publisher Indonesia, 2025)
The advancement of artificial intelligence (AI) technology has transformed the credit scoring system in Indonesia’s fintech peer-to-peer (P2P) lending sector. Automated decision-making increases efficiency and financial inclusion but also raises legal concerns, particularly regarding consumers’ right to obtain explanations for decisions made solely by AI. This study analyzes the legal framework governing the right to explanation and consumer protection in AI-based automated credit assessments within Indonesian P2P lending services. A normative juridical method is applied using legislative, conceptual, and comparative approaches. The findings show that Indonesia has established several legal foundations, including Law No. 27 of 2022 on Personal Data Protection, Law No. 8 of 1999 on Consumer Protection, POJK No. 40 of 2024 on Information Technology-Based Joint Funding Services, and POJK No. 22 of 2023 on Consumer and Community Protection in the Financial Services Sector. However, specific regulation on the right to explanation for AI-generated automated decisions is still lacking. This gap creates challenges in ensuring algorithmic transparency, fairness, and accountability, especially when automated assessments potentially lead to discrimination or inaccurate risk profiling. Therefore, regulatory strengthening is required to mandate the implementation of Explainable Artificial Intelligence (XAI), ensuring that consumers receive understandable information about how decisions are made and possess the right to contest harmful outcomes. Clearer legal mandates are also needed to hold business actors accountable for risks arising from automated decision-making and to protect consumers’ rights in an increasingly digital lending environment.